Simulation tool for learning signals and systems theory – part II - Tan, Sze Yin (Nanyang Technological University, 2023)
This project aims to create a MATLAB-based simulation tool to enhance the learning of the course Signals and Systems. Signals and Systems is a basic course for engineering students, as it serves as a foundation for higher level courses in Signal Processing, Communications and Control. However, students often find that it is hard to visualize the results and hence induce difficulties in their learning process. This simulation tool will cover the topics of Fourier Series and Fourier Transform, which are being taught in the second part of the course IE2110 Signals and Systems provided by Nanyang Technological University.